Analisis Metode Ekskavasi Terowongan Pengelak Bendungan Bener Berdasarkan Data Geologi Teknik - Sasangka, Daru Jaka (BENTANG : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2021)
The Bener Dam Plan, located in Bener District, Purworejo Regency, Indonesia, has a diversion tunnel. Determination of the appropriate excavation method is very important and necessary to maintain effectiveness and efficiency in the process of implementing the circumvention tunnel construction. The determination of the excavation method is also important for the implementation costs calculation. This research aims to support the planning of determining the appropriate excavation method of the Bener Dam Diversion Tunnel as well as what activities are needed to see the geological conditions of rock in the tunnel both above and below the surface for analysis to determine the excavation. The excavation method was determined by empirical method based on the input parameters of rock conditions, i.e. rock quality, density of discontinuity plane in the rock, and rocks compressive strength. The condition of the tunnel alignment is dominated by good quality andesite breccias (good rock). The empirical analysis of the excavation method shows that the Bener Dam Diversion Tunnel mostly requires a very hard type of blasting (blasting). Another type, i.e. the ripping excavation, is also required.